Reproductive Aspects of Mangrove Crabs (Scylla sp.) Caught by Fishermen in the Bagek Kembar Essential Ecosystem Area, West Lombok - Baiq Gina Amalia Niarni; Karnan Karnan; Anindita Suliya Hangesti Mandra Kusuma; Mahrus Mahrus (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Mangrove crabs are a high-value fishery resource that is closely associated with mangrove ecosystems, but their uncontrolled use has the potential to threaten the sustainability of the population. This study aims to analyze the reproductive aspects of mangrove crabs (Scylla sp.) caught by fishermen in the Bagek Kembar Essential Ecosystem Area (KEE), West Lombok, as the basis for sustainable fisheries management. The research was conducted in March-May 2025, using a quantitative survey method and observation-based data collection. The sampling technique in this study is purposive sampling. The observed parameters included gender, carapace width, body weight, gonadal maturity level (TKG), and gonadal maturity index (IKG). Data were analyzed descriptively and inferentially to describe growth patterns and reproductive conditions. The results showed a dominance of females, with a male:female ratio of 0.83:1. The relationship between carapace width and body weight is negative allometric (b < 3), indicating that carapace growth is faster than body weight growth. The distribution of TKG is dominated by TKG I and III, while the average IKG ranges from 2.05–5.72% with a frequency of 80%. The novelty of this research lies in providing location-based mangrove crab reproductive data in essential ecosystem areas that remain limited. The results of the study confirm the importance of regulating catch size and protecting mature gonadal individuals, and recommend further research on seasonal reproductive dynamics to support ecosystem-based fisheries management.